First-principles investigation of bimetallic Janus ScTaCO 2 MXene: Structure, stability, and gas-sensing performance - Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Gonzalo, Fredy M. [UNESP]; Rivera, Victor J.R. [UNESP]; Flores, Efracio M.; Denis, Pablo A.; Sambrano, Julio R. [UNESP] (Elsevier, 2025)
In this study, a first-principles investigation of bimetallic Janus ScTaCO 2 MXene is conducted, a novel two-dimensional carbide with Sc and Ta atoms positioned on opposite layers. This structure features lattice parameters of a = b = 3 . 18 Å and a cohesive energy of − 5 . 80 eV/atom. Phonon dispersion reveals and ab initio molecular dynamics (AIMD) attest to the dynamic and thermal stability of this new material. An indirect band gap is reported, measured at 1.35 eV (2.24 eV) using the PBE (HSE06) method. It exhibits an isotropic onset of optical absorption, starting at 1.4 eV, with an absorption peak in the green-blue range. Evaluating the elastic constants, it was found C 11 = C 22 = 263 . 74 N/m , C 12 = 38 . 45 N/m , and C 66 = 112 . 64 N/m , all fulfilling the Born–Huang criteria, which subsequently result in a calculated Young’s modulus of 258 N/m and a Poisson’s ratio of 0.146. Engaging in gas-sensing performance, gases such as NH 3 , NH 2 CH 3 , NH(CH 3 ) 2 , and PH 3 were examined, revealing adsorption energies between − 0 . 318 and − 0 . 917 eV . Shifts in work-function up to 0.884 eV were noticed, alongside recovery times between 2 . 23 × 1 0 − 7 s for PH 3 and 2 . 57 × 1 0 3 s for NH(CH 3 ) 2 at 300 K, falling below 1 s when the temperature rises to 900 K. Bader charge analysis registered transfers in the range of 0.18–0.22 e . Our thorough analysis seeks to both emphasize the distinct features of Janus MXenes and highlight their importance in environmental monitoring and safety, thus playing a crucial role in public health protection and industrial safety standards.